2015
DOI: 10.1371/journal.pone.0129792
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Predict Negative Results of QuantiFERON-TB Gold In-Tube Test in Patients with Culture-Confirmed Tuberculosis: A Multicenter Retrospective Cohort Study

Abstract: BackgroundInterferon-γ release assays such as the QuantiFERON-TB Gold In-Tube Test (QFT-GIT) are designed to detect Mycobacterium tuberculosis infections, whether latent or manifesting as disease. However, a substantial number of persons with culture-confirmed tuberculosis (TB) have negative QFT-GITs. Information on host factors contributing to false-negative and indeterminate results are limited.MethodsA multicenter retrospective cohort study was performed with 1,264 culture-confirmed TB patients older than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 26 publications
3
44
1
Order By: Relevance
“…While the quality of study participation, analytical procedure, outcome measurement and analysis were mostly good to evaluate among studies, that of the participation rate and the confounding measurement and account were relatively poor. Only 7 14,17,18,20,21,23,25 of 17 studies had a sufficient participation rate, and the rates in the others were under 50%. For confounding measurement and accounting, eight studies did not assess adequately.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…While the quality of study participation, analytical procedure, outcome measurement and analysis were mostly good to evaluate among studies, that of the participation rate and the confounding measurement and account were relatively poor. Only 7 14,17,18,20,21,23,25 of 17 studies had a sufficient participation rate, and the rates in the others were under 50%. For confounding measurement and accounting, eight studies did not assess adequately.…”
Section: Resultsmentioning
confidence: 95%
“…Advanced age. Pooled odds ratio (pooled OR: 2.06, 95% CI 1.68-2.52) of advanced age calculated with raw data available in 5 of the 14 included studies 6,8,15,20,22 showed a significant relationship between advanced age and false negative results with very low heterogeneity (Fig. 2).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies reported that negative bacteria in sputum [3-5], hypoproteinemia [6-8], combined HIV infection [4, 7, 9], anti-TB treatment [10, 11], medical history [8, 12], anemia [6, 13], diabetes [14], parasitic infections [13], noncavitary lesions in the lung [5], fall and winter seasons [15], increased human leukocyte antigen DRB1-0701 allele [16] and non-Hispanic white or Asian ethnicity [6, 9] are risk factors for false negative IGRA. The association between IGRA and age [3, 7-9, 12, 13, 15-18], body mass index [12, 16] and reduced lymphocyte levels [3, 5, 7, 8, 17, 19, 20] is inconsistent among previous studies. Some of these studies were qualitative studies with small samples and did not consider the possibility that different antigen risk factors might have confounded or biased the results.…”
Section: Introductionmentioning
confidence: 99%